Integrative geospatial modeling: combining local and indigenous knowledge with geospatial applications for adaptive governance of invasive species and ecosystem services - Luizza, Matthew Wayne, author; Betsill, Michele, advisor; Evangelista, Paul, advisor; Fernandez-Gimenez, Maria, committee member; Stohlgren, Tom, committee member (Colorado State University. Libraries, 2015)
With an unprecedented rate of global change, diverse anthropogenic disturbances present growing challenges for coupled social-ecological systems. Biological invasions are one such disturbance known to cause negative impacts on biodiversity, ecosystem functioning and an array of other natural processes and human activities. Maps facilitated by advanced geospatial applications play a major role in resource management and conservation planning. However, local and indigenous knowledge are overwhelmingly left out of these conversations, despite the wealth of observational data held by resource-dependent communities and the potential negative impacts biological invasions have on local livelihoods. My integrative geospatial modeling research applied adaptive governance mechanisms of knowledge integration and co-production processes in concert with species distribution modeling tools to explore the potential threat of invasive plants to community-defined ecosystem services. Knowledge integration at the landscape scale in Alaska provided an important opportunity for re-framing risk assessment mapping to include Native Alaskan community concerns, and revealed the growing potential threat posed by invasive aquatic Elodea spp. to Chinook salmon (Oncorhynchus tshawytscha) and whitefish (Coregonus nelsonii) subsistence under current and future climate conditions. Knowledge integration and co-production at the local scale in northeastern Ethiopia facilitated shared learning between pastoral communities and researchers, leading to the discovery of invasive rubber vine (Cryptostegia grandiflora), which was previously unknown to my research team or a number of government and aid organizations working in the region, thus providing a potentially robust early detection and monitoring approach for an invasive plant that holds acute negative impacts on a number of endemic ecosystem service-providing trees. This work revealed knowledge integration and co-production processes and species distribution modeling tools to be complimentary, with invasive species acting as a useful boundary-spanning issue for bringing together diverse knowledge sources. Moreover, bridging and boundary-spanning organizations and individuals enhanced this rapid appraisal process by providing access to local and indigenous communities and fostered a level of built-in trust and legitimacy with them. Challenges to this work still remain, including effectively working at broad spatial and governance scales, sustaining iterative processes that involve communities in validating and critiquing model outputs, and addressing underlying power disparities between stakeholder groups. Top-down, discipline-specific approaches fail to adequately address the complexity of ecosystems or the needs of resource-dependent communities. My work lends evidence to the power of integrative geospatial modeling as a flexible transdisciplinary methodology for addressing conservation efforts in rural regions with mounting anthropogenic pressures at different spatial and governance scales.
Keywords: invasive species; risk assessment; traditional ecological knowledge; local ecological knowledge; environmental management; species distribution modeling